The effect of gonadoliberin analog treatment in precocious puberty on polycystic ovarian syndrome prevalence in adulthood - Orszulak, Dominika; Niziński, Kacper; Bil, Adriana; Gawlik, Aneta; Ziora, Katarzyna; Drosdzol-Cop, Agnieszka (Frontiers in Endocrinology, 2024)
Precocious puberty is diagnosed when pubertal characteristics appear before the age of 8 years in females. The most common form is gonadotropin-dependent, called axial. The primary method of treatment is administration of gonadotrophin-releasing hormone analogues (GnRHa). The aim of the study was to verify hypothesis that GnRHa therapy in the childhood may be of additive risk factor for polycystic ovary syndrome (PCOS) in adulthood.The study group consists of 24 women (median age 22 years, median BMI 23.5) treated with GnRHa for precocious puberty in childhood. The control group includes 40 women (median age 23 years, median BMI 25.6) diagnosed with isolated premature thelarche and not using GnRHa in the childhood. Anthropometric measurements, ultrasound examination of minor pelvis and hormonal profile were performed. PCOS diagnosis was based on Rotterdam criteria.Results: The study confirmed a higher prevalence of PCOS in the study group (50%) than in the control group (10%); p=0.0006. Significant, linear correlation between free testosterone levels and ovarian size was found in the study group (R=0.45 p= 0.03).Conclusions: GnRHa therapy during childhood may have a potential influence on incidence of PCOS in the adulthood. Therefore, in this group of patients long-term follow-up focused on screening for PCOS would seem beneficial.